Anomalous Vertical Structure of Tropospheric Ozone Due To Stratospheric Intrusions and Convective Transport - Zhixiong Chen; Jane Liu; Xiushu Qie; Jianchun Bian; Rubin Jiang; Dan Li; Zhixuan Bai; Hongbo Zhang; Zhuling Sun; Jinqiang Zhang; Xian Xiao; Mengmiao Yang; et al. (Geophysical Research Letters)
Abstract Vertical transport carries airmasses from different sources of tropospheric O3 including photochemical production and stratospheric intrusions, and is crucial for vertical O3 variability. Based on temporally dense ozonesondes over northern China, this study reports an anomalous vertical O3 distribution characterized by a “bottom‐heavy” structure. Specifically, O3 well exceeded the normal values in the middle‐to‐lower troposphere due to the stratospherically intruded airmasses (SIA), but was sharply reduced in the upper troposphere and lower stratosphere region because of convectively lofted air transported from the Tibetan Plateau. Guided by the discovery of such a vertical O3 structure, we further assess the SIA contribution to tropospheric O3 using multi‐year AIRS satellite observations, and find that SIA appear frequently during summer and lead to short‐term O3 enhancements 35% above the normal values at 500 hPa. These results reveal the linkages between vertical O3 variations and synoptic processes, highlighting the non‐negligible contribution of SIA to tropospheric O3.